Research issues in genomic signal processing. - Dougherty, E.R (IEEE Signal processing magazine)
Genomic signal processing (GSP) concerns the processing of genomic signals. It may be defined as the analysis, processing, and use of genomic signals to gain biological knowledge and the translation of that knowledge into systems-based applications. In this article, the authors discuss the key research issues for GSP. It is important to recognize that "genomic signal processing" is not a name for genomic bioinformatics nor for the application of signal processing methods in genomics. We note that the research issues pertaining to GSP fit within the overall challenges confronting research in the area of multimodal biomedical systems.